2022
DOI: 10.1186/s12913-022-07828-3
|View full text |Cite
|
Sign up to set email alerts
|

Key drivers involved in the telemonitoring of covid-19 for self-health management: an exploratory factor analysis

Abstract: Background The recent COVID-19 pandemic and the shortage of general practitioners has determined a strong pressure on the Italian health system. This critical issue highlighted the fundamental support of e-health services not only to lighten the workload of doctors, but also to offer patients a health service tailored to real needs. Therefore, the digital engagement platforms represent a valid aid, as they reconcile the efficiency needs of the healthcare system with the benefits for the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In addition, mental support should be provided through these systems for a better understanding of stressors and vulnerability as well as for providing faster and better psychological screening and tracking. During the COVID-19 crisis, multiple telemonitoring systems were developed to monitor SARS-CoV-2-infected patients in their home environment [ 56 , 57 , 58 ]. These systems should be altered to humanize patient care during the current MPX outbreak but can also be very useful for the management of future viral outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mental support should be provided through these systems for a better understanding of stressors and vulnerability as well as for providing faster and better psychological screening and tracking. During the COVID-19 crisis, multiple telemonitoring systems were developed to monitor SARS-CoV-2-infected patients in their home environment [ 56 , 57 , 58 ]. These systems should be altered to humanize patient care during the current MPX outbreak but can also be very useful for the management of future viral outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the remote delivery of care, whether through telemedicine or phone calls, could bring more opportunities for people struggling with health issues, especially for those who are typically overlooked by the healthcare system, such as people with chronical conditions, mental health issues, aging needs, or special needs [ 12 ]. An offsite model of healthcare services could be beneficial for patients [ 29 , 31 , 40 ] as well as healthcare professionals. The usage of the offsite model of healthcare relies on communication between the patients and the healthcare providers, which can lead to improvements in patient–provider communication and subsequently to a more patient-centered approach [ 22 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent COVID-19 crisis also demonstrated that digital services could not only ameliorate physician workloads, but also offer patients a personalized health service ( 19 21 ). A cohort study in Galicia (Northwestern Spain) proved that proactive at-home telemonitoring of patients with COVID-19, even of those with a high risk for complications, was indeed associated with reduced pressure on hospital capacity and lower mortality rates ( 22 ).…”
Section: Technology-enabled Care As a New Methodology For Preserving ...mentioning
confidence: 99%